Employee Discipline in Improving Public Services at the Yaro District Office in Nabire Regency - Kristoforus M. Bouk; Kornelis Angwarmas (Sean Institute, 2026)
Public service is one indicator of successful governance, especially at the district level, which deals directly with the community. The quality of public service is greatly influenced by the discipline of employees as the main implementers of service. This study aims to analyze employee discipline in improving public service at the Yaro District Office in Nabire Regency, taking into account the geographical conditions of the region, limited office facilities, and employee discipline issues. This study uses a qualitative approach with a descriptive method. The results show that employee discipline at the Yaro District Office is not yet optimal. This is indicated by low employee attendance, the district office often not operating during working hours, and weak employee compliance with work rules. In addition, the remote geographical location, weak supervision, and limited office facilities and infrastructure also contribute to low employee discipline and poor quality of public services. Therefore, consistent enforcement of employee discipline, firm and exemplary leadership, improvement of the service system, and adequate work facility support are needed to improve public services.